2010
DOI: 10.1111/j.1369-1600.2009.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual performance impairments in adult rats trained on an object discrimination task subsequent to cocaine administration during adolescence

Abstract: The present study was conducted to determine whether cognitive impairments in adult rats treated with cocaine during adolescence demonstrated in previous investigations extend to tests of object discrimination learning. Accordingly, 30-day-old male Long-Evans rats were injected subcutaneously with either 10 or 20 mg/kg cocaine or received control injections of saline for 7-8 consecutive days. An extended abstinence period was then introduced (mean = 70.7 ± 9.8 days) before subjects, who were now young adults (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…However, for drugs of abuse, the length of withdrawal may play a major role as the deriving negative emotional state may impinge on cocaine‐induced cognitive deterioration further worsening the pathological outcome. Accordingly, Santucci and Rabidou (2011) have shown that exposure of PND 30 rats to cocaine (10 or 20 mg kg −1 ) for 8 days induces cognitive impairments in early adulthood (Santucci & Rabidou, 2011). In this experiment, the authors tested the animals for the acquisition of a two‐choice object discrimination task.…”
Section: Repeated Exposure Of Adolescent Rats To Cocainementioning
confidence: 99%
“…However, for drugs of abuse, the length of withdrawal may play a major role as the deriving negative emotional state may impinge on cocaine‐induced cognitive deterioration further worsening the pathological outcome. Accordingly, Santucci and Rabidou (2011) have shown that exposure of PND 30 rats to cocaine (10 or 20 mg kg −1 ) for 8 days induces cognitive impairments in early adulthood (Santucci & Rabidou, 2011). In this experiment, the authors tested the animals for the acquisition of a two‐choice object discrimination task.…”
Section: Repeated Exposure Of Adolescent Rats To Cocainementioning
confidence: 99%
“…Human stimulant abusers, who usually initiate drug use in adolescence, have been shown to exhibit significant cognitive deficits that vary in magnitude depending on the duration of drug exposure (Bolla et al, 1998; Verdejo-Garcia et al, 2006). In adult rats exposed to psychostimulants during adolescence, there is evidence of enduring deficits in cognitive tasks that assess attention, fear learning, memory, decision making, and impulse control (Harvey et al, 2009; Santucci and Rabidou, 2011; Sillivan et al, 2011; Hankosky and Gulley, 2012). However, in these studies, it is difficult to ascertain if adolescents are relatively more sensitive to these effects because comparison groups of adult-exposed subjects were rarely utilized.…”
Section: Psychostimulants and Adolescencementioning
confidence: 99%
“…studies, cocaine was associated with deficits in attention, episodic memory, and working memory with moderate and large effect sizes magnitude (Potvin et al, 2014). Hippocampal-dependent cognitive impairment during withdrawal is also well documented in preclinical models (Fijał et al, 2015;Fole et al, 2015;Jordan & Andersen, 2018;Krueger et al, 2009;Ladrón de Guevara-Miranda et al, 2017;Mendez et al, 2008;Mottarlini et al, 2020;Preston et al, 2019;Santucci & Rabidou, 2011). Although these studies were performed with prolonged cocaine administration (8-14 days) than that used in the present study, considering the increase in glucose metabolism induced by CBD in regions known to be affected by cocaine withdrawal, and its neuroprotective profile, we can suggest the benefit of CBD in improving cognitive function of individuals undergoing detoxification.…”
Section: Discussionmentioning
confidence: 99%